A polydopamine nanomedicine used in photothermal therapy for liver cancer knocks down the anti-cancer target NEDD8-E3 ligase ROC1 (RBX1) - Zhanxia Zhang; Junqian Zhang; Jianhui Tian; Hegen Li (Journal of Nanobiotechnology, 2021)
Abstract Knocking down the oncogene ROC1 with siRNA inhibits the proliferation of cancer cells by suppressing the Neddylation pathway. However, methods for delivering siRNA in vivo to induce this high anticancer activity with low potential side effects are urgently needed. Herein, a folic acid (FA)-modified polydopamine (PDA) nanomedicine used in photothermal therapy was designed for siRNA delivery. The designed nanovector can undergo photothermal conversion with good biocompatibility. Importantly, this genetic nanomedicine was selectively delivered to liver cancer cells by FA through receptor-mediated endocytosis. Subsequently, the siRNA cargo was released from the PDA nanomedicine into the tumor microenvironment by controlled release triggered by pH. More importantly, the genetic nanomedicine not only inhibited liver cancer cell proliferation but also promoted liver cell apoptosis by slowing ROC1 activity, suppressing the Neddylation pathway, enabling the accumulation of apototic factor ATF4 and DNA damage factor P-H2AX. Combined with photothermal therapy, this genetic nanomedicine showed superior inhibition of the growth of liver cancer in vitro and in vivo. Taken together, the results indicate that this biodegradable nanomedicine exhibits good target recognition, an effective pH response, application potential for genetic therapy, photothermal imaging and treatment of liver cancer. Therefore, this work contributes to the design of a multifunctional nanoplatform that combines genetic therapy and photothermal therapy for the treatment of liver cancer.